Examiner Variability in Caries Diagnosis of Selected UPCD Students Using International Caries Detection and Assessment System for the Detection of Caries on Occlusal Surfaces/Erine D. Mamaril and Danica Elaine C. Rivera. - Mamaril, Erine D.
INTRODUCTION: To bring forward the current understanding of the process of initiation and progression of dental caries to the fields of epidemiological and clinical research, the International Caries Detection and Assessment System (ICDAS) was developed. This study aimed to assess the performance of selected UPCD students by determining the inter-examiner and intra-examiner variability in diagnosing occlusal caries during the ICDAS II system.